Trichosanthin Inhibits Breast Cancer Cell Proliferation in Both Cell Lines and Nude Mice by Promotion of Apoptosis - Fang, Evandro Fei; Zhang, Chris Zhi Yi; Zhang, Lin; Wong, Jack Ho; Chan, Yau Sang; Pan, Wen Liang; Dan, Xiu Li; Yin, Cui Ming; Cho, Chi Hin; Ng, Tzi Bun (PLOS ONE, 2012)
Breast cancer ranks as a common and severe neoplasia in women with increasing incidence as well as high risk of metastasis and relapse. Translational and laboratory-based clinical investigations of new/novel drugs are in progress. Medicinal plants are rich sources of biologically active natural products for drug development. The 27-kDa trichosanthin (TCS) is a ribosome inactivating protein purified from tubers of the Chinese herbal plant Trichosanthes kirilowii Maximowicz (common name Tian Hua Fen). In this study, we extended the potential medicinal applications of TCS from HIV, ferticide, hydatidiform moles, invasive moles, to breast cancer. We found that TCS manifested anti-proliferative and apoptosis-inducing activities in both estrogen-dependent human MCF-7 cells and estrogen-independent MDA-MB-231 cells. Flow cytometric analysis disclosed that TCS induced cell cycle arrest. Further studies revealed that TCS-induced tumor cell apoptosis was attributed to activation of both caspase-8 and caspase-9 regulated pathways. The subsequent events including caspase-3 activation, and increased PARP cleavage. With regard to cell morphology, stereotypical apoptotic features were observed. Moreover, in comparison with control, TCS- treated nude mice bearing MDA-MB-231 xenograft tumors exhibited significantly reduced tumor volume and tumor weight, due to the potent effect of TCS on tumor cell apoptosis as determined by the increase of caspase-3 activation, PARP cleavage, and DNA fragmentation using immunohistochemistry. Considering the clinical efficacy and relative safety of TCS on other human diseases, this work opens up new therapeutic avenues for patients with estrogen-dependent and/or estrogen-independent breast cancers.